2017
DOI: 10.1099/jgv.0.000957
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of Halictivirus resolves the Sinaivirus phylogeny

Abstract: By providing pollination services, bees are among the most important insects, both in ecological and economical terms. Combined next-generation and classical sequencing approaches were applied to discover and study new insect viruses potentially harmful to bees. A bioinformatics virus discovery pipeline was used on individual Illumina transcriptomes of 13 wild bees from three species from the genus Halictus and 30 ants from six species of the genera Messor and Aphaenogaster. This allowed the discovery and desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 87 publications
2
44
0
Order By: Relevance
“…Similarly, replicative strands of the DWV genome were detected in Myrmica rubra (Schläppi et al, 2019), an invasive species of ant in North America (Groden et al, 2005), and in the Argentine ant Linepithema humile (Sébastien et al, 2015), also one of the most widespread and abundant invasive ant species (Holway et al, 2002). Specific strains of LSV were detected in Messor ant species, which were thought to be genuine infections rather than the result of inter-species transmission (Bigot et al, 2017).…”
Section: Transmission Of Viruses In Non-bee Insects Hymenopteramentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, replicative strands of the DWV genome were detected in Myrmica rubra (Schläppi et al, 2019), an invasive species of ant in North America (Groden et al, 2005), and in the Argentine ant Linepithema humile (Sébastien et al, 2015), also one of the most widespread and abundant invasive ant species (Holway et al, 2002). Specific strains of LSV were detected in Messor ant species, which were thought to be genuine infections rather than the result of inter-species transmission (Bigot et al, 2017).…”
Section: Transmission Of Viruses In Non-bee Insects Hymenopteramentioning
confidence: 94%
“…and Osmia sp. The species Halictus scabiosae, Halictus sexcinctus, and Halictus simplex were screened for viruses by Bigot et al (2017), where the Halictus scabiosae Adlikon virus (HsAV) was described and identified as a virus closely related to LSV. ARV-1/BRV-1 was found in Bombus sp.…”
Section: Transmission Of Bee Viruses In Non-apis Pollinatorsmentioning
confidence: 99%
“…Positive-sense single-stranded RNA viruses comprise the largest group of known honey bee pathogens (reviewed in [27,28]). These include members of Iflaviridae (i.e., deformed wing virus, sacbrood virus, and slow bee paralysis virus), Dicistroviridae (i.e., black queen cell virus, Israeli acute paralysis virus, acute bee paralysis virus, and Kashmir bee virus), chronic bee paralysis virus [29], and Lake Sinai viruses [15,30,31], as well as a growing list of other viruses and virus families (reviewed in [27,28,32]). Viruses are transmitted vertically from parents to offspring and horizontally between bees within the crowded environment of the colony via contact and trophallaxis (mouth to mouth food transfer), as well as via contact with contaminated floral resources while foraging [33,34] (reviewed in [28,35]).…”
Section: Introductionmentioning
confidence: 99%
“…In this review we will use the term “bee virus”, though insect viruses generally have a broad host range and “bee viruses” can infect a variety of bee hosts, as well as ants and mites [ 67 , 68 , 69 , 70 ] (reviewed in [ 66 ]). Because of their role in agriculture, honey bees ( Apis mellifera ) are the most investigated bee species and thus the majority of bee-infecting viruses were discovered in honey bee samples.…”
Section: Introductionmentioning
confidence: 99%